2013
DOI: 10.1021/es4033887
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticles Modify the Antioxidative Stress Enzyme Activities and Macromolecule Composition in Rice Seedlings

Abstract: Cerium oxide nanoparticles (nCeO2) have been shown to have significant interactions in plants; however, there are limited reports on their impacts in rice (Oryza sativa). Given the widespread environmental dispersal of nCeO2, it is paramount to understand its biochemical and molecular impacts on a globally important agricultural crop, such as rice. This study was carried out to determine the impact of nCeO2 on the oxidative stress, membrane damage, antioxidant enzymes' activities, and macromolecular changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(108 citation statements)
references
References 64 publications
11
96
1
Order By: Relevance
“…This is quite possible, because root is primary entry point of NPs (Anjum et al 2013). Our present results are in agreement with the earlier report by Rico et al (2013). They reported that 0.125 g nCeO 2 L -1 induced the higher level of membrane damage in rice roots.…”
Section: Membrane Stability Index and Root Ion Leakagesupporting
confidence: 94%
“…This is quite possible, because root is primary entry point of NPs (Anjum et al 2013). Our present results are in agreement with the earlier report by Rico et al (2013). They reported that 0.125 g nCeO 2 L -1 induced the higher level of membrane damage in rice roots.…”
Section: Membrane Stability Index and Root Ion Leakagesupporting
confidence: 94%
“…The maximum activity of CAT was at 7.0 U mg −1 protein at 1.0 g beaker −1 . These results are comparable with previous studies in which rice and radish seedlings were cultured under the stress conditions of nCeO 2 and Cu 2+ (Rico et al 2013;Sun et al 2010).…”
Section: Responses Of Antioxidant Enzymes In Tomato Seedlingssupporting
confidence: 91%
“…The decrease of SOD activity at the highest dosages (in contrast to the control) suggested that SOD was out of self-adjustment to the stress of the contaminants in the biochar, resulting in the inefficient removal of superoxide. In addition, the results on SOD activity were comparable with previous investigations in which plants were cultured under the stress conditions of heavy metals and PHAs (Rico et al 2013).…”
Section: Responses Of Antioxidant Enzymes In Tomato Seedlingssupporting
confidence: 87%
“…Previous work on non-GM plants reported negative, positive, and/or no effect of different NPs on seed germination, root elongation, and other plant growth performance indicators. ENPs can influence nutrient uptake (Larue et al 2012;Trujillo-Reyes et al 2013), bioavailability (Lee et al 2008;Marusenko et al 2013), biotransformation (Zhang et al 2012(Zhang et al , 2013, antioxidant enzyme activity (Cui et al 2014;Rico et al 2013), and other physiological biomarkers in conventional plants. Fe 2 O 3 NPs specifically have been shown to have key effects on plants.…”
Section: Introductionmentioning
confidence: 99%